TINJAUAN YURIDIS TERHADAP PUTUSAN BEBAS DALAM PERKARA NOMOR 113/PID/2011/PTR TENTANG PEMBUNUHAN BERENCANA - Daulay, Rahmat Tua; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The judiciary is a search for truth and justice, each case in all legal proceedings filed by the law enforcement community must be able to perform legal certainty for every decision the judges who examined the case. Administration of justice, especially at the level of the court can not also ignore the role of law enforcement. To realize an independent judiciary and impartiality need for harmonious integration work between all the law enforcement investigators Prosecutors and Judges. Judge high integrity is indispensable for the realization of a court ruling in accordance with the sense of justice. Acquittal handed down by Judge High Court of Riau with the case number 113 / pid / 2011 / ptr who originally prosecuted in state court defendant Sujarwo Pengaraian sand that has been in the prison sentence by a judge for 17 years with violating Article 340 of Jo Article 55 paragraph (1 ) -1 to the Criminal Code that is murder. From the above results of the exposure, the authors are interested in discussing about the Juridical Review Verdict Against Free In Case No. 113 / Pid / 2011 / Ptr About Murder Plan. The purpose of this study was to determine the law and legal reasoning of the judge in a criminal case number 113 / pid / 2011 / ptr. This study is a descriptive normative research, which consists of primary data, secondary and tertiary. Data collection tools in the form of literature studies or studies document. The data have been collected and grouped be analyzed qualitatively and deductively inferred.Legal consideration by the judges in the case number 113 / PID / 2011 / PTR that no one really convincing evidence that the defendant violated Article 340 of the Criminal Code Sujarwo conjunction with Article 55 paragraph (1) All 2 of the Criminal Code as it has been in previous criminal sentenced by assembly District Court Judge Sand Pengaraian. The judge must not convict to a no two legal evidence.It is better to release a thousand guilty persons than to punish one innocent person.Keywords: Justice, Law Enforcement, Decision